Implementasi L2TP Mikrotik dalam Interkoneksi Site to Site - Harnaningrum, Lucia Nugraheni (JATISI, 2024)
Implementation of L2TP (Layer 2 Tunneling Protocol) in site to site interconnection is a critical effort in maintaining security and reliable connections between two geographically separated networks. It needs to be ensured to transmit data securely. Tests in various conditions are carried out to get maximum results, especially from a security perspective. Variations are made to security configurations and policies. Test results show that L2TP can improve connection security between the two networks. Data sent between networks can be strongly encrypted, reducing the risk of unauthorized access or hacking. The configuration of this protocol is quite complex. In addition, this research also identified important factors that influence the effectiveness of L2TP implementation, such as existing network infrastructure, implemented security policies, and staff understanding of the technology. The results of this research provide recommendations for how organizations can implement L2TP to improve security. This research highlights the importance of considering network security in the context of site to site interconnections and the key role played by L2TP in protecting network connections. This research can provide practical guidance for organizations in strengthening the security of their connections in increasingly complex site-to-site interconnection scenarios